2019
DOI: 10.1155/2019/1761693
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Preoperative Anxiety and ABO Blood Types: Evidence from a Clinical Cross-Sectional Study

Abstract: Gene-environment interaction is identified as the determinant in anxiety. ABO blood types represent a part of the genetic phenotype. Therefore, we assume ABO blood types correlate with preoperative anxiety. This cross-sectional study enrolled 352 patients with different ABO blood types, scheduled for elective surgery between 2018 and 2019 in the First Affiliated Hospital of Shihezi University. HADS (hospital anxiety and depression scale) scores and VA (visual analogue scales for anxiety) scores were all used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Observational studies investigating ABO blood types, preoperative anxiety and phenotypic factors are limited in the literature. To the best of our knowledge, a study examining ABO blood types and preoperative anxiety was found in the literature (11). In this study, POA levels of patients with AB blood group were found to be higher than those with other blood groups (11).…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…Observational studies investigating ABO blood types, preoperative anxiety and phenotypic factors are limited in the literature. To the best of our knowledge, a study examining ABO blood types and preoperative anxiety was found in the literature (11). In this study, POA levels of patients with AB blood group were found to be higher than those with other blood groups (11).…”
Section: Introductionmentioning
confidence: 53%
“…To the best of our knowledge, a study examining ABO blood types and preoperative anxiety was found in the literature (11). In this study, POA levels of patients with AB blood group were found to be higher than those with other blood groups (11).…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…There are different personal factors that could contribute to the level of anxiety, such as gender [5], education level [18], ABO blood types [19], different type of surgeries, and period after surgery [20]. Anxiety in people aged 55 years and above is significantly lower in the married/ cohabitating group than that of the divorced/separated/ widowed group [21].…”
Section: Color Version Available Online Color Version Available Onlinementioning
confidence: 99%
“…This topic received attention by the medical community as early as the 1960s of last century [29] . Recently, a clinical-cross sectional study evaluating the correlation between ABO blood types and preoperative anxiety was carried out [30] . It enrolled 352 patients with different ABO blood types scheduled for elective surgery and found the AB group displayed a high preoperative anxiety level.…”
Section: Abo Blood Group and Affective Dis-ordersmentioning
confidence: 99%